Room-temperature plastic behavior and formability of a commercially pure titanium: Mechanical characterization, modeling, and validation. (1st October 2021) - Revil-Baudard, Benoit; Cazacu, Oana; Massoni, Elisabeth
Highlights: New data on effects of anisotropy and strain path on room-temperature behavior of titanium. Revealed very specific behavior under bulging (sudden thinning; snap failure). Specific behavior cannot be predicted if tension–compression asymmetry neglected. Accurate predictions of level of strains, localization of deformation, orientation of localized zones obtained with CPB06. Abstract: Data on the room temperature behavior of titanium is limited. To assess the anisotropy of the plastic behavior of a commercially pure grade 2 hcp–titanium T40 for different strain paths, in this study both uniaxial tests in various orientations with respect to the rolling direction as well as bulging tests using different die apertures were conducted. Under uniaxial tension, the plastic anisotropy in yielding is moderate, while the anisotropy in plastic strains is very strong. The material also displays tension–compression asymmetry, irrespective of the orientation the flow stress in compression being higher than in tension. The bulging tests data, namely the evolution of the thickness with the fluid pressure complemented with post-test DIC measurements reveal that T40 has unusual deformation and failure characteristics as compared to common materials with cubic crystal structure. Irrespective of the die aperture, instabilities occur suddenly, the reduction in thickness being drastic (snap failure). However, the evolution of strains depends on the die aperture aspect ratio (hemispherical vs. elliptical). The anisotropy of the titanium T40 also leads to a different response depending on the orientation of the material axes with respect to the die axes. To explain these specific characteristics of the behavior of titanium T40 under bulging, two orthotropic criteria were used, one that neglects the tension–compression asymmetry of the material (Hill, 1948) and another that accounts for the combined effects of anisotropy and tension–compression asymmetry (Cazacu et al. (2006) yield criterion). Determination of the parameters involved in both criteria was done using only uniaxial test data. The F.E. results presented show that neglecting the tension–compression asymmetry of T40 leads to less accurate predictions of the fluid pressure and strains at which fracture occurs, and in some cases an incorrect orientation of the zone of localized deformation. Using the Cazacu et al. (2006) criterion, it is possible to accurately predict the sudden occurrence of instabilities, the distribution of plastic strains, and the correct orientation of the zone of localized deformation in both the hemispherical and elliptical bulge tests.